Identification of the most favorable months for coffee trade - Melo, Bruno Manoel Rezende de; Soares de Almeida, Carla; Góes da Silva, Fernanda; da Silva Barbosa, Fernando; Goulart Castro, Douglas; Ribeiro, Leonardo (Revista Agrogeoambiental, 2023)
Coffee is traded on a stock exchange on which the goods are priced and influence their value both in the physical market and in the futures market, which causes doubts in coffee growers about the most opportune moment for trading. Then, the goal of this work was to consider the most favorable and unfavorable months over the years for the arabica and robusta coffee trading in the physical market and arabica coffee in the future market. The work was carried out using historical data on the price of coffee in Brazil, stratifying it into periods and listing for each year of evaluation the percentage of months with the first and second highest and lowest prices. Arabica and Robusta coffee were assessed respectively from 2018 to 1981 and from 2018 to 1995. Arabica coffee in the futures market was analyzed from 2018 to 1980. The evaluation was performed using descriptive statistics and correlation analysis among the modalities of coffee trading in Brazil. Great instability was observed between the months of high and low prices for coffee trading. This shows the uncertainties existing in the market; however, it is possible to observe a trend of the most favorable and unfavorable months for commercialization. It is determined that for arabica coffee, December and January are the most favorable and unfavorable months for trading, respectively. For robusta coffee, the most favorable and unfavorable sales months were June and January. Arabica coffee in the futures market January was the best month for trading and February in the opposite condition, in alternate years, the least favorable month.